PENGARUH PERSEPSI DIFERENSIASI PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN ALAT KONTRASEPSI JENIS KONDOM MEREK DUREX DAN FIESTA (SUATU STUDI PADA PENDUDUK KOTA BANDUNG UTARA) - Djatnika Dwi Asri; Dewi Indriani; Wildan Taufik (JURISMA : Jurnal Riset Bisnis & Manajemen, 2012)
ABSTRACT"The Influence of Perceptions of Product Differentiation and Brand Image on Purchase Decisions Contraception Type Brand Durex Condoms and Fiesta. (A Study at population of North Bandung City) ". Thesis, Management Studies Program, Strata 1, Faculty of Economics, University Computer Indonesia, under the guidance of Hj. Dewi Indriani, S.E., M.Sc.This study aims to determine the response of respondents to product differentiation type of contraceptive and condom brand Durex Fiesta, as well as how large the influence of product differentiation and brand image against the decisions of consumers in the purchase of contraceptives type of Durex brand condoms and Fiesta.The research method used is descriptive analysis method and analysis verifikatif. Descriptive analysis method was used to clarify the picture of research variable by using frequency and percentage distribution tables. While the analytical methods used to test the hypothesis verifikatif research using relevant statistical tests.The results obtained can be known to have a strong relationship between product differentiation and brand image with consumers purchasing decisions either partially or simultaneously. Factors to consider in the implementation of product differentiation and reinforce brand image is more to know the characteristics and needs of consumers.Keywords: Product differentiation, brand image and consumers decisions